EMG circuit design and AR analysis of EMG signs - Hardalaç, Firat; Canal, Rahmi (My University, 2004)
In this study, electromyogram (EMG) circuit was designed and tested on 27 people. Autoregressive (AR) analysis of EMG signals recorded on the ulnar nerve region of the right hand in resting position was performed. AR method, especially in the calculation of the spectrums of stable signs, is used for frequency analysis of signs, which give frequency response as sharp peaks and valleys. In this study, as the result of AR method analysis of EMG signals frequency-time domain, frequency spectrum curves (histogram curves) were obtained. As the images belonging to these histograms were evaluated, fibrillation potential widths of the muscle fibers of the ulnar nerve region of the people (material of the study) were examined. According to the degeneration degrees of the motor nerves, nine people had myopathy, nine had neuropathy, and nine were normal.
Keywords: AR (autoregressive); electromyogram (EMG); fibrillation; histogram; potential